What drives banks' geographic expansion? The role of locally non-diversifiable risk - Ulrich Schüwer; Reint E. Gropp; Felix Noth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Why do some banks react to deregulation by expanding geographically while others do not? This paper examines this question using exogenous variation in locally non-diversifiable risk that banks face in their home state. As a measure of locally non-diversifiable risk we use data on damages arising from natural disasters in the U.S. Combining this data with information on the staggered deregulation in the 90s, we find that banks facing such risks expand significantly more into other states after deregulation than banks that do not face such risks. Only large banks are able to take advantage of deregulation, small banks are not. Finally, banks that do expand, do not necessarily seek to reduce their exposure to risk when expanding.
Keywords: G21; G28; G20; 330